Laparoscopic gastric surgery for cancer: where do we stand? - Antonakis, Pantelis T; Ashrafian, Hutan; Isla, Alberto Martinez (World J Gastroenterol, 2014)
Gastric cancer poses a significant public health problem, especially in the Far East, due to its high incidence in these areas. Surgical treatment and guidelines have been markedly different in the West, but nowadays this debate is apparently coming to an end. Laparoscopic surgery has been employed in the surgical treatment of gastric cancer for two decades now, but with controversies about the extent of resection and lymphadenectomy. Despite these difficulties, the apparent advantages of the laparoscopic approach helped its implementation in early stage and distal gastric cancer, with an increase on the uptake for distal gastrectomy for more advanced disease and total gastrectomy. Nevertheless, there is no conclusive evidence about the laparoscopic approach yet. In this review article we present and analyse the current status of laparoscopic surgery in the treatment of gastric cancer.
Keywords: Accreditation; Certification; Clinical Competence; Education, Medical, Graduate; Gastrectomy; Humans; Laparoscopy; Learning Curve; Lymph Node Excision; Practice Guidelines as Topic; Robotic Surgical Procedures; Robotics; Stomach Neoplasms; Treatment Outcome